Nematology - Concepts, Diagnosis and Control 2017
DOI: 10.5772/intechopen.69164
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Useful Rhizosphere Microorganisms for Nematode Control

Abstract: Nematodes are very diverse and parasitize various plants including vegetables, and their management is of concern. Biological control of nematodes provides an environmentally friendly management option and there are various micro-soil-borne organisms which can be considered for this purpose. The primary goal of this chapter is to provide a review on the progress made so far, in application of biological control agents in nematode management in vegetables, cereals, and root and tuber crops. This chapter will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 150 publications
0
16
0
1
Order By: Relevance
“…In our study, the plant-mediated effect on the parasitic nematodes depended on the plant species from which the microbiome was transplanted. This effect might be harnessed to engineer soil microbiomes by selected crops towards increased plant resistance against plant-parasitic nematodes ( Nyaku et al, 2017 ). However, a trade-off between induced resistance and plant growth was often reported ( Huot et al, 2014 ; Vyska et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the plant-mediated effect on the parasitic nematodes depended on the plant species from which the microbiome was transplanted. This effect might be harnessed to engineer soil microbiomes by selected crops towards increased plant resistance against plant-parasitic nematodes ( Nyaku et al, 2017 ). However, a trade-off between induced resistance and plant growth was often reported ( Huot et al, 2014 ; Vyska et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Root damage in association with the withdrawal of plant nutrients finally leads to plant damage and yield losses. Globally, crop losses associated with plant-parasitic nematodes are estimated to be 12.6% corresponding to $216 billion per year ( Nyaku et al, 2017 ). However, damage by plant-parasitic nematodes often remains unnoticed as aboveground symptoms are rare and a proper diagnosis for nematodes is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants rely on their root microbiome when they are under attack by pathogens and parasites, leading to a selective enrichment of plant-protective microbes and microbial activities in the rhizosphere (Bakker et al, 2018). The importance of the rhizosphere microbiome in plant-nematode interactions has been extensively reviewed (Kerry, 2000;Griffiths et al, 2007;Sikora et al, 2007;Nyaku et al, 2017;. Importantly, some recent studies have demonstrated that the transfer of the rhizosphere microbiome from one crop to another significantly alleviated nematode infection and enhanced the plant resistance to PPN (Elhady et al, 2018;Zhou et al, 2019).…”
Section: Importance Of the Rhizosphere Microbiota In Plant-nematode Imentioning
confidence: 99%
“…Among the biotic factors, the plant parasitic nematodes (PPNs) are a major biotic constraint to wheat production systems worldwide, especially where the plants under stress by other biotic and abiotic factors, particularly drought. PPNs cause severe annual economic losses of up to 216 billion USD worldwide when simultaneously exposed to drought (Nyaku et al, 2017). Cereal cyst nematodes (CCNs) [Heterodera avenae Wollenweber, 1924 (Tylenchida: Heteroderidae) group], among the PPNs, are most commonly found in wheat cropping areas (Rivoal & Cook, 1993;Dababat & Fourie, 2018).…”
Section: Introductionmentioning
confidence: 99%